1996
DOI: 10.1055/s-2007-999037
|View full text |Cite
|
Sign up to set email alerts
|

Gene Defects in Congenital Factor XIII Deficiency

Abstract: The knowledge of the molecular basis of factor XIII deficiency has improved significantly in recent years. Almost 20 different mutations have been described in the gene coding for the factor A-subunit and 3 mutations in the gene coding for the B-subunit. Half of the mutations in the factor XIIIa A-subunit gene are nonsense mutations that result in premature termination of translation. Three of them are frameshift mutations that are caused by minor deletions. Two of them are splicing mutations and 3 are stop mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 24 publications
(53 reference statements)
1
7
0
Order By: Relevance
“…Since then molecular genetic analysis has demonstrated that FXIII deficiency is a highly heterogenous disorder. The gene defects causing FXIII deficiency were last summarized by Mikkola & Palotie (1996). The number of mutations responsible for FXIII deficiency has more than doubled since then.…”
Section: Sequence Changes Causing Fxiii Deficiencymentioning
confidence: 99%
“…Since then molecular genetic analysis has demonstrated that FXIII deficiency is a highly heterogenous disorder. The gene defects causing FXIII deficiency were last summarized by Mikkola & Palotie (1996). The number of mutations responsible for FXIII deficiency has more than doubled since then.…”
Section: Sequence Changes Causing Fxiii Deficiencymentioning
confidence: 99%
“…3,4 In more than 30 unrelated patients the genetic defect(s) responsible for severe FXIII deficiency have been identified. 5,6 In addition to pathogenic mutations, a number of polymorphisms have been identified in the amino acid sequence of FXIII-A. [7][8][9][10] The biochemical effect of these polymorphisms has not been explored.…”
Section: And Muszbek Et Al 2 )mentioning
confidence: 99%
“…In the last few years several research teams have elucidated the genetic defects causing factor XIII defi ciency. [24][25][26][27][28][29][30] Up to now 10 missense, 6 nonsense muta tions, and 2 splicing defects have been found. In homo zygous patients all mutations caused failure of translation and expression of factor XIII subunit A.…”
Section: Congenital Factor XIII Deficiencymentioning
confidence: 99%